Analisis Triple Bottom Line Menggunakan Analytical Hierarchy Process: Studi Kasus di Sebuah Perusahaan Circuit Breaker - Shania Paramitha Kusuma; Seong Uook (Universitas Bunda Mulia, 2021)
Sustainability in a company is the main component so that it can run in a long term of time. This also measures how a company can last and survive in a world of globalization where everything feels so fast. One of the systems to measure this competition using the Triple Bottom Line (TBL) System. This system looks up to 3 aspects that have to be the main focus for the company there were economic, environment and social. This circuit breaker company wants to know if they were capable enough to implement a triple bottom line in their product type 1160. First of all, in order to implement this system, collect data from economic, environment and social aspect. After that, conduct an interview with managers of the company to ask about their view on implementing triple bottom line in economy, environment and social aspect. Next, is to process the data using Analytic Hierarchy Process (AHP) method and give weight on each indicator or criteria that were chosen before and process matrix equation using microsoft excel. The result showed sequentially that circuit breaker company focusing on the social aspect with value 0.46, 0.36 on economic and 0.18 on environment aspect. It means that circuit breaker company still thinks that employee welfare is a priority in order to produce product type 1160. Keywords: sustainability, triple bottom line, analytic hierarchy process, employee welfare.